Tree–litter–soil system C:N:P stoichiometry and tree organ homeostasis in mixed and pure Chinese fir stands in south subtropical China - Zhang, Han; Li, Xian; Wang, Shengqiang; Jiang, Chenyang; Cui, Yuhong; Fan, Rongyuan; Lan, Yahui; Zhang, Qianchun; Ye, Shaoming (Frontiers in Forests and Global Change, 2024)
Cultivation of Chinese fir (Cunninghamia lanceolata) have alleviated timber shortages and mixed stands with Chinese fir and indigenous species represent a sustainable forestry model. Studying system nutrient balance and tree nutrient homeostasis can provide insights into the ecological advantages of Chinese fir mixed stands and guide the management of plantations. Mixed Chinese fir plantations with two native broadleaf species (Michelia macclurei and Mytilaria laosensis) and pure Chinese fir stands were examined for our study. The responses in carbon (C), nitrogen (N) and phosphorus (P) distribution and their stoichiometric characterization in the tree-litter-soil system to stand changes were evaluated.In addition, the ecological stoichiometric homeostasis of leaves, branches, trunks, bark and roots was used to measure the trees' adaptive capacity to stand changes. The results showed that the mixed stands of Michelia macclurei and Chinese fir significantly increased soil OC, TN and TP, and improved the carbon sequestration and nutrient storage functions of the plantations. The mixed stands improved the litter mass and C:N and C:P to different degrees. The soil N and P imbalance reduced the leaf N:P, resulting in N limitation of different trees, while the principal component analysis showed that the improvement of soil TN in the mixed plantation alleviated the N limitation. In addition, mixed stands reduced N, P, and N:P homeostasis in branch, trunk, and bark of some Chinese fir trees, whereas mixed species showed flexibility in leaf N:P homeostasis. Therefore, the selection of mixed species for mixed forests is a critical factor to consider when creating mixed plantations. These results contribute to our understanding of the ecological stoichiometry of fir plantations and are of considerable importance for the sustainable development of plantations as well as for the response to global climate change.